Leukotrienes as mediators in ischemia-reperfusion injury in a microcirculation model in the hamster. - Lehr, H A (1991)
Leukotriene (LT)B4 promotes leukocyte chemotaxis and adhesion to the endothelium of postcapillary venules. The cysteinyl leukotrienes, LTC4, LTD4, and LTE4, elicit macromolecular leakage from this vessel segment. Both leukocyte adhesion to the endothelium and macromolecular leakage from postcapillary venules hallmark the microcirculatory failure after ischemia-reperfusion, suggesting a role of leukotrienes as mediators of ischemia-reperfusion injury. Using the dorsal skinfold chamber model for intravital fluorescence microscopy of the microcirculation in striated muscle in awake hamsters and sequential RP-HPLC and RIA for leukotrienes, we demonstrate in this study that (a) the leukotrienes (LT)B4 and LTD4 elicit leukocyte/endothelium interaction and macromolecular leakage from postcapillary venules, respectively, that (b) leukotrienes accumulate in the tissue after ischemia and reperfusion, and that (c) selective inhibition of leukotriene biosynthesis (by MK-886) prevents both postischemic leukotriene accumulation and the microcirculatory changes after ischemia-reperfusion, while blocking of LTD4/E4 receptors (by MK-571) inhibits postischemic macromolecular leakage. These results demonstrate a key role of leukotrienes in ischemia-reperfusion injury in striated muscle in vivo.